Intervensi Head Up 15-30 Derajat Terhadap Perfusi Serebral Pasien Traumatic Brain Injury: Studi Kasus - Saputra, La Ode Agustino; Hafid, Muh. Anwar; Jamaluddin, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2024)
Background: Head injury or traumatic brain injury (TBI) is a traumatic disorder in brain function, either accompanied by bleeding or without bleeding in brain tissue. The incidence of head trauma is estimated at 500,000 cases annually with a mortality rate of more than 10% of patients dying before arriving at the hospital and more than 100,000 patients experiencing various disabilities. The phenomenon found in the field was that patients with head injuries due to traffic accidents who were treated in the ICU room at Labuang Baji Hospital Makassar, experienced cerebral perfusion disorders, decreased consciousness and some patients experienced headaches as a result of ineffective cerebral perfusion. The main treatment for head injury patients is increasing O2 status and positioning the patient with a head up of 15-300. Methods: the research method used is a case study method by carrying out the nursing process starting from assessment to evaluation in cases of traumatic brain injury in the Intensive Care Unit (ICU) room at Labuang Baji Hospital Makassar. Results: The nursing diagnoses found were the risk of ineffective cerebral tissue perfusion, impaired physical mobility, risk of nutritional deficit, and risk of infection. Discussion: head up intervention 15-300 can smooth cerebral perfusion and reduce intracranial pressure through several mechanisms, namely lowering blood pressure, changes in ventilation, increasing venous flow through unvalved jugular veins, thereby reducing central venous blood volume which reduces intracranial pressure. Transfer of CSF from the intracranial compartment to the spinal subarachnoid space1 can reduce intracranial pressure and improve cerebral perfusion. Conclusion: head up intervention 15-300 is effective to overcome the problem of ineffective cerebral perfusion risk.